Comparison of methods of isolating extracellular vesicle microRNA from HepG2 cells for High-throughput sequencing - Xiong, Ying-Hui; Fan, Xue-Gong; Chen, Ya-Yu; Huang, Yan; Quan, Jun; Yi, Pan-Pan; Xiao, Mei-Fang; Huang, Ze-Bing; Hu, Xing-Wang (Frontiers in Molecular Biosciences, 2022)
Abstract: (1) Background: Extracellular vesicles (EVs) were reported to participate in various cellular processes based on the biomolecules, particularly microRNAs. Numerous commercial EVs isolation reagents are available. However, whether these reagents are suitable for separating Evs from the culture supernatant of model cell lines, such as HepG2, and whether the isolated products are suitable for High-throughput sequencing remains unclear; (2) Methods: We examined three commonly used EVs isolation kits: the ExoQuick-TC exosome precipitation solution (EQ), Total Exosome Isolation from cell culture medium (EI), and exoEasy Maxi Kit (EM), to isolate EVs from HepG2 cell culture medium supernatants. EVs were identified based on marker proteins, particle size measurements, and electron microscopy analysis. The total amounts of microRNA and microRNA High-throughput sequencing data quality from EVs isolated by each kit were compared; (3) Results: The total amount of EVs’ microRNA isolated from the EI and EM groups were higher than that obtained from the EQ group (EQ/EI: p =0.036, QI/EM: p =0.024). High-throughput sequencing data quality evaluation showed that the EI group possessed higher quality than those in the EM group; (4) Conclusions: For the cell culture medium from HepG2, EVs’ microRNA isolated by EI reagents might be more suitable for High-throughput sequencing applications.